Against the tide. Chinese workers and entrepreneurs in Spain facing the economic crisis (2007-2013) - Beltrán Antolín, Joaquín; Sáiz López, Amelia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2015)
From a comparison of the effects of the economic crisis (2007-2013) in Spain on the national population and foreign workers and those of Chinese origin, highlights the differential behavior of the latter, against the tide of job loss. The Chinese workers and entrepreneurs increase steadily consolidating and deepening strategies prior to insertion into the Spanish labor market through the development of ethnic economic niches where ownership of family business is the dominant model. The coincidence of the beginning of the economic crisis (2007) with the opening of a new ethnic niche waiting to expand, with a reduction of the initial costs of their business, has allowed an acceleration in access to ownership of family business.